PENGARUH MODEL PEMBELAJARAN TERPADU BERBASIS MASALAH TERHADAP KEMAMPUAN LITERASI DAN NUMERASI SISWA KELAS V DI SD NEGERI 2 BAUMATA TIMUR - Heryon Bernad Mbuik, Rasty Mardiwati Crisna Ndolu,Godelifa Kofi; Karolina Trifonia Kutiom , Yefi Hermena Lifu; Devita Deku, Kristoforus Lakumau; Florence Mayela Manehat, Yuliga Getriana Helle (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of a problem-based integrated learning model on the literacy and numeracy skills of fifth-grade students at SD Negeri 2 Baumata Timur. The background of the research was based on the pre-observation findings showing low student literacy and numeracy performance, suspected to be due to conventional learning methods. The method applied in this research is quasi-experimental, utilizing a control group design with measurements taken before and after the intervention.Instruments used were literacy and numeracy tests administered before and after the intervention. Students in the experimental group, who were exposed to the problem-based integrated learning model, demonstrated notably greater gains in literacy and numeracy than those in the control group. The findings support the use of this model as an effective strategy for enhancing foundational student competencies.